Pneumonia and HIV Types: A Case Control Study in Gadarif State, Sudan - Elbashir, Salwa Abdelrahman Hamd; Abakar, A. D.; Nour, Bakri Y. M. (British Journal of Healthcare and Medical Research, 2022)
Background: Pulmonary infections remain one of the most important causes of morbidity and mortality among HIV patients, and the first cause of hospital admission in the HAART era. Achieving an etiological diagnosis of pulmonary infection in these patients is important due to its prognostic consequences. This is a case control study conducted at ART Center in Gedarif Teaching Hospital between the periods January 2020 to October 2021. Oro pharyngeal swabs were collected for isolation and identification of organisms from fifty HIV patients suffering from pneumonia with ages from 15 years old to 65 years old were included in this study to elicit the microorganism insulted to pneumonia among them. And also to detect types of HIV which are most associated with those pneumonic patients. Results: The results revealed that all pneumonic patients were type (1) HIV patients (100%), the most common microorganisms isolated were Staphylococcus auras (60%), Haemophilus influenzeae (20%), Pseudomonas aerugnosa (18%),and Streptococcus pneumonia (2%). Conclusion: This study indicated that all HIV patients are type 1, and revealed that the most common cause of pneumonia in HIV infected patients was Staphylococcus auras. So Accurate diagnosis, and appropriate treatment and prevention of HIV-associated opportunistic pneumonias is an important strategy for reducing the morbidity and mortality associated with HIV/AIDS.